Research on focal nodular hyperplasia with MSCT and postprocessing - Liu, Yuan-Jian (The WJG Press and Baishideng, 2009)
AIM: To investigate and evaluate the pathological features and diagnostic value of focal nodular hyperplasia (FNH) with multi-section spiral computed tomography (MSCT) and postprocessing. METHODS: A total of 25 patients with FNH who had undergone MSCT and postprocessing were included in the investigation. All patients had been pathologically or clinically confirmed with FNH. A number of 75 cases of hepatic carcinomas, hemangiomas and adenomas were randomly selected at a same period for a comparative study. RESULTS: There was a single focus in 22 cases and multiple foci in 3 cases. On the plain scan, 17 lesions showed hypodensity, 7 isodensity and 4 hyperdensity (the case with fatty liver). With contrast, 28 lesions were enhanced evenly or in the nodules in the arterial phase; 13 lesions still showed hyperdensity, 11 lesions isodensity and 4 lesions hypodensity in the parenchymatous phase; in the delayed phase only 5 lesions showed hyperdensity but 9 lesions showed isodensity or slight hypodensity and 14 lesions showed hypodensity. Twelve lesions of 28 had central asteroid scars. Thickened feeding arteries in postprocessing were seen in 24 lesions, and were integrated into the parenchymatous lesions with a gradual and smooth course. On the contrary, there were no artery penetrated into the lesion found in any of comparative hepatic tumors. CONCLUSION: Doctors could make a correct diagnosis and differentiation of FNH on evaluation of the characteristic appearance on MSCT with postprocessing.